The Empowerment of Sukoharjo Magpie Breeders in The Role of Strengthening Production Capacity and Financial System Management - Hermawan, Iwan; Suharmanto, Suharmanto; Hindrawati, Gita; Sartono, Sartono; Inayah, Inayah; Rahmawati, Lusiana (International Journal of Research and Community Empowerment, 2024)
The bird industry has a promising opportunity because in a year it can generate a turnover of 1.7 trillion, so the bird business is much favored by the community. One of the bird breeding UD Murai Batu Tarto Jaya., can earn a turnover of 50-80 million per month. This turnover can still grow, but there is a market gap of 20%. This gap occurs due to market demand that is not met because the production approach is still manual and the condition of the birdhouse space is inadequate. Another problem is the inseparable use of finances between business and household needs, which results in unmeasured financial performance and causes difficulties in accessing business capital loans from financial institutions. This community service aims to provide solutions for strengthening production capacity through improved incubation techniques, clean production-based birdhouse design, strengthening the managerial side through a simple financial system implementation package, and entrepreneurial management training. The method used in building a complete solution in this community service acquired Borg and Gall R&D with the calculation of the questionnaire used to measure the achievement of knowledge and skills induction based on the three-box method. The implementation of the community service program has shown an increase in the skills of partner SMEs by 87%, an increase in knowledge by 88.09%, and the development of ideas for sustainability by 96.3%, as well as providing instrument strengthening by providing automatic hatching machines and cages.  This community service provides a complete solution to strengthening the production and management of financial systems in Murai Batu Tarto Jaya SMEs.